Police Human Resource Planning: National Surveys, 2011-2013 (United States and Canada) - Cordner, Gary W. ([Verlag nicht ermittelbar], 2016)
This study utilized: a national survey of law enforcement officials; a national survey of criminal justice faculty; a survey of criminal justice students at Arizona State University, Kutztown University, Michigan State University, and Sam Houston State University; four separate surveys of a small expert panel; and mini-case studies to investigate issues associated with police human resource management and planning, such as recruitment, selection, training, and promotion.